A brief overview of clinical significance of novel Notch2 regulators. (2nd September 2020) - Pancewicz, Joanna
ABSTRACT: The Notch pathway is an essential signaling system allowing neighboring cells to communicate and accomplish their proper developmental role in physiological condition. Nevertheless, there are many controversies conferring its function in pathological condition, particularly in cancer. It has been discovered that epigenetic regulation, posttranslational modifications, gene overexpression, and mutations may lead to the dysregulation of the Notch pathway. Additionally, Notch-mediated signaling can support tumor-suppressing mechanisms in certain types of cancer or may have oncogenic functions in others. Notch2 is one of the receptors commonly expressed in a variety of cancer cells, including gastric, hematological, and lung cancer. Moreover, it can be dysregulated in other diseases. In efforts to explain the role of Notch2 in the pathogenesis of cancer, recent studies indicated an association between this receptor and dysregulation of miRNAs, tumor-associated stromal cell, and modulation in tumor cells. Consequently, Notch2 function in the carcinogenesis process is unquestionable, whereas information according to the effect of its inhibition in tumor is still obscure. Hence, the aim of our study was to evaluate the current state of knowledge conferring Notch2 inhibition, with a particular focus on its role in cancer.